The development and validation of the Short Language Measure (SLaM): A brief measure of general language ability for children in their first year at school. Issue 3 (11th February 2020) - Matov, Jessica; Mensah, Fiona; Cook, Fallon; Reilly, Sheena; Dowell, Richard
Abstract: Background: There is no sufficiently accurate short‐language measure that could be used by speech–language pathologists, teachers or paraprofessionals to screen young school‐aged children to identify those requiring in‐depth language evaluations. This may be due to poor development of the available measures, which have omitted crucial test development steps. Applying more stringent development procedures could result in a measure with sufficient accuracy. Aims: To create and validate a short‐language measure that has acceptable accuracy, validity and reliability, and which can be used to identify children who require further assessment and/or referral to speech–language services. Methods & Procedures: The study consisted of two phases. In Phase 1 (measure creation), 56 children were assessed with 160 direction‐following and sentence‐recall test items and a reference measure, the Clinical Evaluation of Language Fundamentals—Fourth Edition (CELF‐4). Items were then examined for their individual characteristics (validity, reliability, difficulty and discrimination) via item analysis and the highest quality items were selected to form the Short Language Measure (SLaM). In Phase 2 (measure validation), 126 children were assessed with the SLaM and the reference measure (CELF‐4) to determine SLaM's accuracy, validity and reliability. Outcomes & Results: A total of 40 test items were selected to form SLaM in Phase 1. Findings from Phase 2 indicated that SLaM had an accuracy of 94% (sensitivity = 94%, specificity = 93%), validity of 0.89 and reliability of 0.93. These values remained relatively consistent across both phases. Conclusions & Implications: The results indicated that SLaM has excellent psychometric properties. It can be used to identify children who need further evaluation by a speech–language pathologist. What this paper adds: What is already known on this subject Prior research suggests that combining a direction‐following and a sentence‐recall task has sufficient discrimination accuracy and agreement with an omnibus language measure. Trialling a large set of direction‐following and sentence‐recall test items to select those with the highest individual characteristics could result in an effective short‐language measure. What this paper adds to existing knowledge A short‐language measure (SLaM) was created and validated on two independent samples of children. Items with the highest validities, reliabilities and discrimination capacities were selected to form SLaM. This procedure resulted in a measure with high validity and reliability that exceeded the criterion for adequate discrimination accuracy. What are the potential or actual clinical implications of this work? SLaM is an effective measure that can accurately identify children who require detailed evaluations by speech–language pathologists.